Social Security Fund as a Form of Constitutional Responsibility for the Right to Health - Sisca F Usman (BPJS Kesehatan, 2021)
Health is one of the human rights that has been recognized and enshrined in the constitutions of many countries. To achieve a high level of health, Indonesia is not unlike many countries that have implemented and ensured the sustainability of social security programs in the health sector. This requires a stable source of fund. This study aims to compare the recognition of the right to health in the constitutions of developed and developing countries and sources of funding for social security for health programs using a literature review method. Developing and developed countries have recognized the right to health in their constitutions and regulate the social security system. There are many ways to regulate the sources of fund for social security programs. The state pays the contribution for their employers and for the poor, as well as providing financial support for implementing social security programs. Keywords: constitution; contribution in social security funding; social health insurance; the right to health